Kernel Cob And Little Miss Sweetclover - Mitchell, George, 1873-1967; Sarg, Tony, 1882-1942 (Salt Lake City, UT : Project Gutenberg, 2004)
"KERNEL COB AND LITTLE MISS SWEETCLOVER" by George Mitchell is a children's fantasy tale published in the early 20th century. The story revolves around the imaginative adventures of two siblings, Jackie and Peggs, who create dolls named Kernel Cob and Little Miss Sweetclover. Their fond memories and desires prompt them to embark on whimsical quests to find their lost parents, invoking themes of childhood innocence and creativity. The opening of the book introduces Jackie and Peggs, who, living in a quaint white house with their forgetful aunt, find themselves creating their own toys out of the natural elements around them. Jackie constructs a soldier named Kernel Cob using corn, while Peggs crafts a flower doll she names Sweetclover. As they play, they express their wishes to have their parents back, initiating a dialogue with their newfound dolls that are imbued with life. Thus, the stage is set for a fantastical journey where the dolls and children explore their world in search of love, companionship, and family, igniting readers' imaginations with the promise of adventure ahead. (This is an automatically generated summary.)
Release date is 2004-11-23
E-text prepared by Gretchen Phillips, The Internet Archive Children's Library
Keywords: Fantasy literature; Adventure stories; Voyages and travels -- Juvenile fiction; Dolls -- Juvenile fiction